Penerapan Tehnik Dasar Dribling dan Passing Stoping Pada Siswa SMA Negeri 1 Jangka Buya Pada Tahun 2023 - Mirza (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2023)
ABSTRACT The researchers conducted this research to find out the level of basic skills in applying dribbling and passing stopping at SMA Negeri 1 Jangka Buya. After being given treatment, the aim to be achieved was to find out how high the level of dribbling and passing stopping skills of SMA Negeri 1 Jangka Buya students was. This type of research is descriptive research. The research population is the research population, namely the total number of students at SMA Negeri 1 Jangka Buya, totaling 158 students. The sample used in this research was 26 students using a cluster random sampling technique. The data analysis technique used was descriptive statistical statistics with percentages. The results of the research show that the level of basic skills in playing soccer for class IX students at SMA Negeri 1 Jangka Buya is sufficient. The results obtained for students' passing stopping skills were 12.5% in the "very good" category, 23.53% in the "good" category, 36.76% in the "fair" category, 25% in the "poor" category and 2.21% in the "poor" category. very little." The results obtained for the dribbling skills of students at SMA Negeri 1 Jangka Buya are sufficient. This can be seen from the results obtained by male and female students as many as 7.35% in the "very good" category, 13.23% in the "good" category, 53.68% in the "fair" category, 20.59% in the "poor" category and 5.15% category "very little